Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

[tex]\[
9 \times (2x - 1) = 3^4 - 2x
\][/tex]


Sagot :

Let's solve the given equation step-by-step:

[tex]\[ 9 \times (2x - 1) = 3^4 - 2x \][/tex]

1. Calculate [tex]\(3^4\)[/tex]:
[tex]\[ 3^4 = 81 \][/tex]

So, the equation becomes:
[tex]\[ 9 \times (2x - 1) = 81 - 2x \][/tex]

2. Distribute 9 on the left side:
[tex]\[ 9 \times (2x - 1) = 9 \times 2x - 9 \times 1 \][/tex]
[tex]\[ 18x - 9 = 81 - 2x \][/tex]

3. Combine like terms by adding [tex]\(2x\)[/tex] to both sides:
[tex]\[ 18x - 9 + 2x = 81 - 2x + 2x \][/tex]
[tex]\[ 20x - 9 = 81 \][/tex]

4. Isolate the term with [tex]\(x\)[/tex] by adding 9 to both sides:
[tex]\[ 20x - 9 + 9 = 81 + 9 \][/tex]
[tex]\[ 20x = 90 \][/tex]

5. Solve for [tex]\(x\)[/tex] by dividing both sides by 20:
[tex]\[ x = \frac{90}{20} \][/tex]
[tex]\[ x = 4.5 \][/tex]

Therefore, the solution to the equation is:

[tex]\[ x = 4.5 \][/tex]